Fluid/s : come, piss, spit; rivers, lakes, sea : exploring queer, brown, male identity in Aotearoa/New Zealand through abject, queer, feminist, and decolonisation theory : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Irvine, Elton (Massey University, 2021)
I am spent. My puku distended, the bloat of my gut stretches the skin, my innards pushing out, the soft fat pushed to hard. There is a comfort in this tension; my clothes hold me; the fabric stretches to the shape of my body. My belly filled to bursting with the essence of the gods and deities of my people. I am full to bursting, but (do) I want some more(?) From our most intimate of spaces: of memories best not remembered come words spoken, that are, perhaps, best not be spoken. Aligning memory with a physical here and now, fluid(s) acts to the abject of bodily fluids, to the concrete materiality of natural bodies of, and to the state of being fluid, slipping eel slide slick, between one, and the other.
Keywords: Māori Masters Thesis; 360603 Performance art